Applying the responsibility accounting system to maximize tax revenue and its role in achieving sustainable development - Abdul Hussein Idan, Abdul Mahdi; Kadhim, Ezzaddin (Technium Social Sciences Journal, 2025)
This research is an attempt to demonstrate the role of using liability accounting in the General Tax Authority as an effective tool for control and performance evaluation to contribute to maximizing tax revenues as a means to achieve sustainable development. Liability accounting has a pivotal role in enhancing tax revenues by improving transparency, efficiency, and fairness in the tax system. It also contributes to channeling these revenues towards projects that support the Sustainable Development Goals, promoting long-term economic, social, and environmental growth. By adopting the principles of accountability of responsibility, it enables governments to balance increased tax revenues with sustainable development. Liability accounting is an important tool to enhance tax revenues and support the achievement of the Sustainable Development Goals. SDGs) by enhancing transparency, accountability, and efficiency in the management of public resources, they can contribute to the development of tax revenues as a major resource of the budget, and thus direct them towards sustainable development projects. The research showed that enhancing transparency in accountability would help improve the management of public resources, including tax collection and spending. This enhances citizens’ confidence in the tax system and encourages voluntary compliance with tax laws and tax participation. The research further showed that accountability helps in determining responsibilities and evaluating performance, as a control tool to ensure that government entities act responsibly in managing tax revenues.